PENERAPAN GERAKAN LITERASI POJOK BACA UNTUK MENUMBUHKAN MINAT BACA SISWA KELAS I SDI PERMATA NUSANTARA PADA KEGIATAN KAMPUS MERDEKA - Zul fitria; zainal arif; Resti Septiani (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2022)
BSTRACTThe purpose of this study was to find out with the literacy movement reading corners can be used as an alternative and supporter to increase students' reading interest. The reading corner literacy movement encourages students to always have a thirst for knowledge, makes them happy to read and finally students have broader insights and get new information for class II at Permata Nusantara Islamic Elementary School. This research was conducted at Permata Nusantara Islamic Elementary School involving 40 students. The research method used for data collection Data collection in this study used observation sheets, interviews, and documentation. The data analysis technique uses data reduction, data presentation, and drawing conclusions.